1999
DOI: 10.1017/s000711459900063x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrate in man: friend or foe?

Abstract: Based on the premise that dietary nitrate is detrimental to human health, increasingly stringent regulations are being instituted to lower nitrate levels in food and water. Not only does this pose a financial challenge to water boards and a threat to vegetable production in Northern Europe, but also may be eliminating an important non-immune mechanism for host defence. Until recently nitrate was perceived as a purely harmful dietary component which causes infantile methaemoglobinaemia, carcinogenesis and possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
164
0
10

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(174 citation statements)
references
References 79 publications
(111 reference statements)
0
164
0
10
Order By: Relevance
“…They are recirculated in the blood, concentrated in the salivary glands, secreted in saliva and reduced to nitrites by facultative Grampositive anaerobes (Staphylococcus sciuri and S. intermedius) on the tongue. Owing to the acidic stomach environment, the salivary nitrites are reduced to large quantities of nitric oxide (NO) and other oxides of nitrogen (16). NO is a potent vasodilator which plays a key role in the control of vascular tone and is released by endothelial cells from L-arginine.…”
Section: Discussionmentioning
confidence: 99%
“…They are recirculated in the blood, concentrated in the salivary glands, secreted in saliva and reduced to nitrites by facultative Grampositive anaerobes (Staphylococcus sciuri and S. intermedius) on the tongue. Owing to the acidic stomach environment, the salivary nitrites are reduced to large quantities of nitric oxide (NO) and other oxides of nitrogen (16). NO is a potent vasodilator which plays a key role in the control of vascular tone and is released by endothelial cells from L-arginine.…”
Section: Discussionmentioning
confidence: 99%
“…Although NO 2 can be converted to nitrosamine in the stomach (McKnight et al 1999), the concentration of NO 2 in nature is too low to pose a problem in this respect (Table 1). Therefore, it is hard to consider environmental NO 2 as a risk factor, since even high-incidence ESCC areas do not have high concentrations of NO 2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…van Loon et al (1998) showed that NO 3 has no harmful effect, even when intake is high. However, when NO 3 is assimilated in the body, it is converted to NO 2 by denitrifying bacteria, and NO 2 can subsequently be converted to nitrosamine in the stomach (McKnight et al 1999). Consequently, a high concentration of NO 3 will lead to a high incidence of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, indicam que dietas ricas de saladas e vegetais e, portanto, alto conteúdo de nitrato são protetoras contra alguns tipos de câncer, particularmente câncer gástrico (ADDISCOTT & BENJAMIN, 2000;ARCHER, 2002). Porém, MCKNIGHT et al (1999) mostram que experimentos tentando ligar o aparecimento de câncer à dieta rica em nitratos têm demonstrado resultados contraditórios (Tabela 1).…”
Section: Conteúdo De Nitrato Em Alface Cultivada Em Hidroponia No Brasilunclassified